Edukasi Tentang Pemanfaatan Kalender Menstruasi Berbasis Android Bagi Kemudahan Remaja - Nurqalbi SR; Rismawati Rismawati (Lembaga Pengembangan Kinerja Dosen, 2024)
In order to improve the community development business system so that it is more productive and efficient, technology is needed. The introduction of technology that has developed in society is technology that has been developed in a modern way, or what is known as